Design of Batik Dhemar Kambhang Information Media Based on Observational Documentary Film - Hujairi, Ahmad Walid; Khoironi, Khoironi; Anugerah, Ahmed David (Journal Research of Social Science, Economics, and Management, 2025)
Dhemar Kambhang Batik is a typical batik from Sumenep Regency, Madura, which has a unique motif and deep philosophy, namely as a "lit lantern" which means the light of life. However, the lack of media information about batik means that it is not widely known by the public. This research aims to design information media based on observational documentary films to introduce Dhemar Kambhang Batik to the public. The method used is the Multimedia Development Life Cycle with stages: concept, design, material collection, design, testing and distribution. This documentary film directly involves batik owners and cultural observers in Sumenep to provide complete and accurate information. Test results on 50 respondents showed that this documentary film was very informative with a respondent satisfaction level of 3.4 (category "satisfied" or "good") and a success rate of 94%. Positive assessments were also given by cultural experts and film experts, who stated that the storyline, shooting techniques and delivery of information were good and easy to understand. With an observational approach, this film succeeds in presenting information about the history, manufacturing process and development of Dhemar Kambhang Batik in an interesting and informative manner.